Prática pedagógica do professor iniciante na rede municipal de ensino de Ponta Grossa/PR - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2017)
This study aims to discuss the pedagogical practice of the beginnings teachers in the first years of the public elementary education in the city of Ponta Grossa, Paraná (BRA). The research is justified by the discussions about the beginning teachers increased sharply in the last years, seen as an important phase for the development of the teacher´s career. The problematic of the research is: How does the pedagogical practice of the beginning teacher in the first years of the public elementary education take place in the city of Ponta Grossa? The research objects were: a) to reveal the factors that determine the practice; b) identify what are the difficulties of beginning teachers finding in their pedagogical practice in first years of teaching; c) identify the theoretical and methodological strategies that beginner teachers use to overcome the problems and difficulties perceived in pedagogical practice. Throughout the research process were discussed the following concepts: beginning teacher and professional insertion (MARCELO 1999; VAILLANT; MARCELO, 2009, 2012; HUBERMAN, 2013); pedagogical practice (GIMENO SACRISTÁN, 1999; VASQUEZ, 2011); organizational atmosphere and school characteristics (BRUNET, 1992; NÓVOA, 1992); the beginning teacher’s knowledge and the relations with the pedagogical practice (BISSOLI DA SILVA, 2006; ROMANOWSKI, 2007; SAVIANI, 2012). Discussions about the beginning of teaching that permeate the Brazilian National Education Program and the Brazilian National Curricular Guidelines for the Initial and Continuous Formation for Elementary Education Teachers are presented. Also compose the discussions of this work: the supervised internship (SILVA, 2011); the possibility of research in teachers training process (LÜDKE, 1993, 2001; ANDRÉ, 2006; GASPARIN, 2002) and the concept of habitus (BOURDIEU, 1983, 2009). Qualitative research was used to investigate the data, which were obtained by the questionnaire and the Discussion Group, from Wivian and Pfaff (2010), Callejo (2001) and Gutiérrez (2001). The research was carried out with 21 public school teachers of Ponta Grossa, Paraná, located in 18 schools. The Content Analysis (2011) was used for the analysis and treatment of the data. The results showed that the practice of the beginning teachers is determined by the knowledge built in the initial formation, and that the difficulties perceived in their practices are related to the interactions with the other teachers of the school and the organizational atmosphere. The beginning teachers seek by themselves to research the theoretical and methodological subsidies to overcome the obstacles perceived, and so they prosecute their pedagogical practice since the presuppositions of the initial formation and by interacting with the coworkers.
Pedagogical practice of the beginning teacher of the public elementary education in Ponta Grossa (BRA) city
Keywords: Formação de professores; Professor iniciante; Prática pedagógica; Teacher training; Beginning Teacher; Pedagogical practice; CNPQ::CIENCIAS HUMANAS::EDUCACAO